Društvo "Z vadbo do cilja" - Pleša, Jernej (Šport (Ljubljana), 2022)
»Z vadbo do cilja« is an organization, founded in 2021. Its vision is to help athletes, active individuals and general population achieve their goals related to sport, movement, physique or health. Members of the organization are employed by different sport organizations as a strength and conditioning coaches, where they work with professional and youth athletes, helping them to successfully participate in their sport and achieve their true physical potential. Members are also working with general population through education courses and a variety of individual and group training treatments with the goal to spread the awareness of the positive effects of healthy and active lifestyle. In addition, we are cooperating with one of the universities in the region, where students can come to our organization as a part of their practical courses and learn about different aspects of coaching and working with different population. The future goals of the organization are to expand its activates within sport clubs, as well as expend its network with various companies and sport organizations in the region, in order to spread the awareness about importance of the regular physical activity and healthy lifestyle for work and life quality. The vision of the organization is to encourage people to engage in regular physical activity, and to teach them how to move safely and effectively to achieve their personal goals. You can read more about the organization on the website https://zvadbodocilja.si/ and follow its activities via the social networks Instagram and Facebook under the name: Z vadbo do cilja.
Keywords: društva; gibanje; kineziologija; šport; trening; vadba